The geochronology of the granitic rocks along the Bear–Slave Structural Province boundary, northwest Canadian Shield - Frith, Rosaline; Frith, R. A.; Doig, R. (Canadian Journal of Earth Sciences, 1977)
Archean granitic rocks along the southern Bear–Slave boundary fall into three age groups: the oldest are 3000 Ma old intrusive tonalites and granodiorites that form the basement to the Yellowknife Supergroup; the second are syn-volcanic granitic intrusions of ~ 2700 Ma; and the youngest are ~ 2560 Ma granitic and migmatitic diapirs formed in part from supracrustal and granitic rocks. Two Proterozoic thermal events are recognized within the Slave Province. A ~ 2300 Ma event may be related to early rift breakup of the Archean crust and is recorded in Rb–Sr whole-rock and K–Ar mineral systems. A ~ 1970 Ma event was less intense but may be related to further rifting of the Archean and to fault-block depression of the Indin Lake supracrustal basin, the intrusion of a group of granodioritic stocks, and the formation or granitic pegmatite.Within the Bear Province, evidence of a ~ 2700 Ma intrusive event and a ~ 2300 Ma thermal event are preserved in Rb–Sr whole rock systems. Practically all the granitic rocks of the Bear Province, including the Hepburn batholitic rocks, are thought to have been derived wholly or partly from Archean rocks. The main period of Hudsonian deformation and metamorphism was accompanied by a diapiric remobilization of the Archean basement about 1800 Ma ago. Twelve Rb–Sr isochrons, as well as other published geochronologic data from the region, support these conclusions.